Retrospective analysis of self-reporting pain scores and pain management during head and neck IMRT radiotherapy: A single institution experience. Issue 2 (May 2017) - O'Connor, P.; Bisson, J.; Asplin, P.; Gahir, D.
Abstract: Aims: Head and neck carcinomas are relatively rare in the United Kingdom with an estimated 9000 cases diagnosed annually. However, pain associated with disease and treatment side effects such as oral mucositis present a major issue for therapy radiographers in providing effective care and maintaining radiotherapy treatment compliance, all factors that can compromise patient outcome if not managed appropriately. Method: This retrospective analysis of self-reporting pain scores collected during a course of radiotherapy aims to assess the perceived pain intensity scores in 30 patients. Data was collected during radiographer review sessions held weekly to determine if any variables to perceived pain scores occurred during a course of radiotherapy. Results: As treatment progressed, the self-reporting pain scores within the cohort increased, in week one the total cohort pain score was 35, this increased to 114 in week 3 and in the final week had totalled 151. An escalation in pain was observed in week 3 of treatment possibly as a result of radiation induced inflammation alongside cytotoxic chemotherapy. Conclusions: The findings of this study provide further evidence to an individualised approach to patient pain relief and providing regular on treatment reviews, thus maintaining patient comfort and ensuring continued treatment compliance. Highlights: Pain is an important but too infrequently analysed symptom in head and neck cancer. As treatment progressed, the self-reporting pain scores within the cohort increased. These findings provide the rationale for an individualised approach to pain relief. Ensuring adequate pain control can positively influence continued treatment compliance.